Telecommunications in the Uruguay Round - Christoph Dörrenbächer; Oliver Fischer (Intereconomics, 1990)
Within the Uruguay Round, the “Group of Negotiations on Trade in Services” deals with the formation of a multilateral framework of principles and rules for the “progressive liberalization” of trade in services. Telecommunications is of high priority in the framework preparations, both as a delivery vehicle for information-intensive services and as a service industry itself. This article attempts to clarify possible economic and developmental opportunities for LDCs which could emerge from the Uruguay negotiations regarding telecommunications and information-intensive services. It contains an up-to-date analysis of the present results of the Uruguay Round and offers an outlook on the consequences of the negotiations.
Keywords: 330; GATT